2013
DOI: 10.1111/ctr.12170
|View full text |Cite
|
Sign up to set email alerts
|

Successful conversion to belatacept after thrombotic microangiopathy in kidney transplant patients

Abstract: Thrombotic microangiopathy (TMA) is a severe complication of kidney transplantation. TMA may occur de novo or as recurrent disease post-transplant. De novo disease is usually associated with immunosuppressive drugs or can be seen as a part of endothelial damage that accompanies antibody-mediated rejection. Treatment for de novo TMA is limited to plasma exchange and change in immunosuppression. We report two cases of de novo TMA post-transplant that were successfully treated by converting to belatacept for main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 32 publications
0
18
0
1
Order By: Relevance
“…Although the use of belatacept is associated with an increased risk of aTCMR, it has been shown to be a good alternative in KTRs with a contraindication to CNIs. Multiple studies have reported successful conversion to belatacept in KTRs with CNI-induced nephrotoxicity, impaired allograft function, delayed graft function, CNI-mediated thrombotic microangiopathy, or atypical hemolytic uremic syndrome [65][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80][81][82]. Furthermore, KTRs with poorly controlled diabetes mellitus while receiving CNI therapy may benefit from belatacept [83,84].…”
Section: Clinical Outcomes After Conversion To Belatacept In Kidney Tmentioning
confidence: 99%
“…Although the use of belatacept is associated with an increased risk of aTCMR, it has been shown to be a good alternative in KTRs with a contraindication to CNIs. Multiple studies have reported successful conversion to belatacept in KTRs with CNI-induced nephrotoxicity, impaired allograft function, delayed graft function, CNI-mediated thrombotic microangiopathy, or atypical hemolytic uremic syndrome [65][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80][81][82]. Furthermore, KTRs with poorly controlled diabetes mellitus while receiving CNI therapy may benefit from belatacept [83,84].…”
Section: Clinical Outcomes After Conversion To Belatacept In Kidney Tmentioning
confidence: 99%
“…Yapılan olgu sunumlarında, Belatacept'e dönüşüm yapılan olguların izleminde TMA' nın düzeldiği ve izlemde tekrar gelişmediği gözlenmiştir (32). Enfeksiyon gelişim riski açısından bakıldığında; Bassil ve ark.…”
Section: Türk Nefroloji Diyaliz Ve Transplantasyon Dergisi Turkish Neunclassified
“…9,73 In the setting of renal transplant, substituting calcineurin inhibitors with belatacept, a selective costimulation blocker, has been shown to be successful in abating TMA in several cases and is recommended if it is safe to do so (high risk of posttransplant lymphoproliferative disorder in Epstein-Barr virusenegative recipients). 74 Many infections have been reported in conjunction with TMA. However, causal association is difficult to determine.…”
Section: Care Pathway 4 (Precipitating Factors)mentioning
confidence: 99%